Will a Recovery of Real Wages Obstruct Progress Toward Disinflation? - Steven B. Kamin; John M. Roberts (American Enterprise Institute (AEI), 2023)
Many observers, including officials at the Federal Reserve, have focused on the need for wages to decelerate if progress toward reducing inflation is to be sustained. We agree that current elevated rates of wage growth would not be consistent with the Fed's 2 percent inflation target in the longer run, and so would eventually need to come down. At the same time, however, real wages have suffered over the past couple of years, suggesting a potential tension between the goals of returning inflation to the Fed's longer-run goal and restoring real wages to their pre-Covid trend. In this note, we use a macroeconomic simulation model to explore different ways in which the gap between real wages and their trend could be resolved and their implications for inflation, unemployment, and interest rates. We find that if both firms and their employees are indifferent to the level of the wage gap, as standard models generally assume, future increases in unemployment and consequent declines in nominal wage gains will lead to declines in inflation but no progress on the wage gap. Conversely, if employees seek to make up for lost wage growth and restore their share of income while firms seek to maintain their current elevated markups, the result is likely to be stagflation: a wage-price spiral and a sharp increase in unemployment. Finally, if elevated markups put downward pressure on prices, disinflation can be achieved along with further solid wage growth that restores wages to their pre-Covid trend. This felicitous outcome would be reinforced if, as evidence suggests, recent price increases reflect to an important degree tight product markets, so that a weakening in aggregate demand leads to rapid disinflation.
Keywords: 330